Detection of Borrelia burgdorferi Sensu Lato and Relapsing Fever Borrelia in Feeding Ixodes Ticks and Rodents in Sarawak, Malaysia: New Geographical Records of Borrelia yangtzensis and Borrelia miyamotoi - Lau, Alice C. C.; Qiu, Yongjin; Mohamed Abdallah, Mohamed Moustafa; Nakao, Ryo; Shimozuru, Michito; Onuma, Manabu; Mohd-Azlan, Jayasilan; Tsubota, Toshio (MDPI AG, 2020)
Members of the Borrelia burgdorferi sensu lato (Bbsl) complex are etiological agents of Lyme disease (LD), and Borrelia miyamotoi is one of the relapsing fever Borrelia (RFB). Despite the serological evidence of LD in Malaysia, there has been no report from Sarawak, Malaysian Borneo. Thus, this study aimed to detect and characterize Borrelia in rodents and Ixodes ticks from primary forests and an oil palm (OP) plantation in Sarawak. Borrelia yangtzensis (a member of the Bbsl complex) was detected in 43.8% (14/32) of Ixodes granulatus; most of the positive ticks were from the OP plantation (13/14). Out of 56 rodents, B. yangtzensis was detected in four Rattus spp. from the OP plantation and B. miyamotoi was detected in one rodent, Sundamys muelleri, from the primary forest. Further, the positive samples of B. yangtzensis were randomly selected for multilocus sequence analysis (MLSA). The MLSA results of successfully amplified tick samples revealed a clustering with the sequences isolated from Japan and China. This study is the first evidence of B. miyamotoi, a known human pathogen in Malaysia, and B. yangtzensis, which is circulating in ticks and rodents in Sarawak, Malaysian Borneo, and presenting a new geographical record of the Borrelia spp.